COMPARISON OF THE COMPOSITION OF SAMPLES SPIRITS FOR PRODUCTION OF PISCO OR GRAPE BRANDY BY MASS SPECTROSCOPY - Garrido S., Alberto (2008)
The Mass spectroscopy analysis of some types of Piscos Peruvians and two adulterated samples, prepared by an addition of sugar to the skins and the other by adding sugar-cane alcohol, have reported interesting evidence of a difference in composition at the adulterated samples. They are compounds such as furfural, the acetate and others, which have not been detected in the pisco prepared correctly and what could be attributed as products of the fermentation of sucrose, sugar, which should not be in the musts Grape where there are only fructose and glucose. The developed method allows not only the correct identification of the components of our Pisco, which once established, could be a way that allows to differentiate it from other spirits and pisco adulterated.